Biodegradable double-network GelMA-ACNM hydrogel microneedles for transdermal drug delivery - Lin, Wensheng; Lin, Shixian; Zhou, Xingwu; Yang, Fanwen; Lin, Zishan; Li, Shiqing; Zhang, Haoyuan; Ouyang, Yuehan; Zhu, Jieying; Sun, Wei; Huang, Dequn; Liao, Baojian; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
As a minimally invasive drug delivery platform, microneedles (MNs) overcome many drawbacks of the conventional transdermal drug delivery systems, therefore are favorable in biomedical applications. Microneedles with a combined burst and sustained release profile and maintained therapeutic molecular bioactivity could further broaden its applications as therapeutics. Here, we developed a double-network microneedles (DN MNs) based on gelatin methacrylate and acellular neural matrix (GelMA-ACNM). ACNM could function as an early drug release matrix, whereas the addition of GelMA facilitates sustained drug release. In particular, the double-network microneedles comprising GelMA-ACNM hydrogel has distinctive biological features in maintaining drug activity to meet the needs of application in treating different diseases. In this study, we prepared the double-network microneedles and evaluated its morphology, mechanical properties, drug release properties and biocompatibility, which shows great potential for delivery of therapeutic molecules that needs different release profiles in transdermal treatment.